Effects of differential stretching protocols during warm-ups on high-speed motor capacities in professional soccer players - Little, T.; Williams, A. G. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to examine the effects of different modes of stretching within a pre-exercise warm-up on high-speed motor capacities important to soccer performance. Eighteen professional soccer players were tested for countermovement vertical jump, stationary 10-m sprint, flying 20-m sprint, and agility performance after different warm-ups consisting of static stretching, dynamic stretching, or no stretching. There was no significant difference among warm-ups for the vertical jump: mean ± SD data were 40.4 ± 4.9 cm (no stretch), 39.4 ± 4.5 cm (static), and 40.2 ± 4.5 cm (dynamic). The dynamic-stretch protocol produced significantly faster 10-m sprint times than did the no-stretch protocol: 1.83 ± 0.08 seconds (no stretch), 1.85 ± 0.08 seconds (static), and 1.87 ± 0.09 seconds (dynamic). The dynamic- and static-stretch protocols produced significantly faster flying 20-m sprint times than did the no-stretch protocol: 2.41 ± 0.13 seconds (no stretch), 2.37 ± 0.12 seconds (static), and 2.37 ± 0.13 seconds (dynamic). The dynamic-stretch protocol produced significantly faster agility performance than did both the no-stretch protocol and the static-stretch protocol: 5.20 ± 0.16 seconds (no stretch), 5.22 ± 0.18 seconds (static), and 5.14 ± 0.17 seconds (dynamic). Static stretching does not appear to be detrimental to high-speed performance when included in a warm-up for professional soccer players. However, dynamic stretching during the warm-up was most effective as preparation for subsequent high-speed performance.